2006
DOI: 10.1079/bjn20051608
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of negative energy balance using doubly labelled water in elite Kenyan endurance runners prior to competition

Abstract: Previous studies have found Kenyan endurance runners to be in negative energy balance during training and prior to competition. The aim of the present study was to assess energy balance in nine elite Kenyan endurance runners during heavy training. Energy intake and expenditure were determined over 7 d using weighed dietary intake and doubly labelled water, respectively. Athletes were on average in negative energy balance (mean energy intake 13 241 (SD 1330) kJ/d v. mean energy expenditure 14 611 (SD 1043) kJ/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
87
3
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(109 citation statements)
references
References 28 publications
12
87
3
7
Order By: Relevance
“…Previous research has suggested that the self-reported TEI bias can be as high as 34% (Ebine et al, 2000;Fudge et al, 2006;Hill et al, 2002), which appears likely in the present study. These data confirm that caution should be taken when interpreting food diaries from athletes, even when considerable care has been taken by the athlete and the practitioner to complete them accurately.…”
Section: Kg)supporting
confidence: 49%
“…Previous research has suggested that the self-reported TEI bias can be as high as 34% (Ebine et al, 2000;Fudge et al, 2006;Hill et al, 2002), which appears likely in the present study. These data confirm that caution should be taken when interpreting food diaries from athletes, even when considerable care has been taken by the athlete and the practitioner to complete them accurately.…”
Section: Kg)supporting
confidence: 49%
“…Ambos os processos envolvem componentes perceptivos, emotivos e cognitivos, ainda pouco explorados (30) . O comportamento do sub-relato é comum entre atletas (31)(32)(33)(34) . No estudo de Edwards et al (31) , utilizando o método da água duplamente marcada, foi observado que corredoras apresentam ingestão energética inferior (32%) ao gasto energético.…”
Section: Discussionunclassified
“…Os autores atribuíram o sub-relato ao comportamento de sub-registro, uma vez que o peso dos atletas não sofreu alteração (33) . Já no estudo de Fudge et al (34) também foi observado sub-relato por parte de corredores quenianos que reduzem, propositalmente, a sua ingestão calórica no período que antecede a competição. Entretanto, nesse último estudo (34) o sub-relato foi, principalmente, associado ao subconsumo.…”
Section: Discussionunclassified
“…Apoyando esta afirmación, los dos estudios de corredores kenianos de resistencia (Fudge et al, 2006y Onywera et al, 2004 Las comidas eran básicamente pan, arroz hervido, patata hervida, avena, repollo, alubias rojas y ugali (densa masa de pasta de maíz). La carne (principalmente de ternera) era servida en el campamento cuatro veces por semana y consumida en escasa cantidad (aproximadamente 100 gramos al día), aunque los atletas podían acceder a más carne y a otros alimentos cuando visitaban sus hogares rurales.…”
Section: La Insatisfacción Con Los Resultados Genéticosunclassified
“…Durante el día también consumían una cantidad significativa de té (con leche). En cuanto a una suplementación alimenticia, los corredores kenianos no tomaban ningún tipo de suplementos (Fudge et al, 2006y Onywera et al, 2004.…”
Section: La Insatisfacción Con Los Resultados Genéticosunclassified